2019
DOI: 10.1111/josh.12823
|View full text |Cite
|
Sign up to set email alerts
|

Students Seeking Mental Health Services at School‐Based Health Centers: Characteristics and Utilization Patterns

Abstract: BACKGROUND: School-based health centers (SBHC) can address unmet mental health needs. Little is known about how students seek care from different providers at SBHCs. We describe and compare how students' SBHC visits differ for students seen by mental health providers (MH group) relative to students seen only by primary care providers (PC group). METHODS:Using administrative data with ICD-9 codes from 9 SBHCs in Denver, Colorado serving youth 10-19 years old during the 2014-2015 school year, we analyzed predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Increased adolescent mental health conditions and severity may demonstrate the longitudinal impact of the COVID-19 pandemic, involving exacerbated stress and life disruption related to familial death, contagious fear, isolation, and instability in daily life. 4,7,8,24 Ongoing surveillance should be implemented to monitor adolescent trends in mental health following the COVID-19 pandemic. This study provides practical implications for schools to consider adolescent mental health trends in resource allocation and interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased adolescent mental health conditions and severity may demonstrate the longitudinal impact of the COVID-19 pandemic, involving exacerbated stress and life disruption related to familial death, contagious fear, isolation, and instability in daily life. 4,7,8,24 Ongoing surveillance should be implemented to monitor adolescent trends in mental health following the COVID-19 pandemic. This study provides practical implications for schools to consider adolescent mental health trends in resource allocation and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…experiencing unstable peer and family relationships, school dropout, suicide, substance use disorder, unemployment, homelessness, and engaging in risky behaviors across the lifespan. [7][8][9] The COVID-19 pandemic exacerbated risk factors-including increased social isolation, contagious fear, household and personal stress and anxiety, and decreased stability in relationships and safety-leaving adolescents vulnerable to mental health conditions. 1,7,[10][11][12][13][14] In response to increasingly alarming mental health trends, the American Academy of Pediatrics, American Academy of Child and Adolescent Psychiatry, and the Children's Hospital Association declared the children's mental health crisis as a national emergency in October 2021.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about predictors of better or worse implementation climate or leadership in schools: some studies suggest that school demographics (such as racial composition, percentage of special education students, and school size) have a negligible effect on schools’ ability to support EBP implementation ( Lyon et al, 2022 ; Thayer et al, 2022 ), while others suggest potential differences in the inner context due to school location or size ( Moore et al, 2021 ; Suhrheinrich et al, 2021 ). In terms of linkages between strategic organizational factors and EBP implementation, studies have found mixed support in clinical settings ( Meza et al, 2021 ; Powell et al, 2021 ) as well as in schools.…”
Section: Introductionmentioning
confidence: 99%
“…Partnerships between schools and local community providers have expanded, as demonstrated by the marked increase in school‐based health centers (SBHCs), often the sole providers of primary care, behavioral health, and dental services for children in a given community 2,6‐12 . There is evidence that SBHCs and school‐based mental health programs increase access to needed care, and improve health outcomes and academic performance 13‐19 …”
mentioning
confidence: 99%